PERKEMBANGAN HUBUNGAN ROMANTIS ANTARA TEMAN TUNARUNGU DAN TEMAN YANG DAPAT MENDENGAR BERDASARKAN TEORI PENETRASI SO - Vincentio Patriciano; Sihombing, Doan Monang Yan Hero; Rachmad, Teguh Hidayatul (Jurnal Spektrum Komunikasi, 2024)
People with disabilities are still often faced with stigma and negative stereotypes from society, they often experience difficulty communicating with other people. These communication difficulties create obstacles in building strong social relationships, so that communication becomes the most important aspect of interactions for people with disabilities. Communication has an important role as a process of creating relationships in social life, including romantic relationships. The importance of communication in romantic relationships has been the focus of this research which aims at exploring the progression of relationships between deaf-hearing couples based on social penetration theory. This research used a qualitative descriptive method with semi-structured interviews with four deaf-hearing couples. Data validity was guaranteed through source triangulation and analysis using coding. The results will describe the progression of the romantic relationship of deaf-hearing couples based on social penetration theory. This research is useful in providing a clear picture of the progression, dynamics and stages of communication that have taken place in the romantic relationship of deaf-hearing couples. The research results show that there is a progression of relationships in accordance with social penetration theory, starting from the orientation phase, exploratory affective exploration, stable exchange, until finally the deepest phase of stable exchange. This research also obtained results that are in accordance with the depth of information from the social penetration theory that applies to the romantic relationships of deaf-hearing couples, namely public layer, personal layer and inner core.